Differential effects of wake promoting drug modafinil in aversive learning paradigms - Shanmugasundaram, Bharanidharan; Korz, Volker; Fendt, Markus; Braun, Katharina; Lubec, Gert (Frontiers in Behavioral Neuroscience, 2015)
Modafinil (MO) an inhibitor of the dopamine transporter was initially approved to treat narcolepsy, a sleep related disorder in humans. One interesting “side-effect” of this drug, which emerged from preclinical and clinical studies, is the facilitation of cognitive performance. So far, this was primarily shown in appetitive learning paradigms, but it is yet unclear whether MO exerts a more general cognitive enhancement effect. Thus, the aim of the present study in rats was to extend these findings by testing the effects of MO in two aversive paradigms, Pavlovian fear conditioning (FC) and the operant two-way active avoidance (TWA) learning paradigms. We discovered a differential, task-dependent effect of MO. In the FC paradigm MO treated rats showed a dose-dependent enhancement of fear memory compared to vehicle treated rats, indicated by increased context-related freezing. Cue related fear memory remained unaffected. In the TWA paradigm MO induced a slight, but significant decrease of avoidance responses compared to vehicle treated animals, while the number of escape reactions during the acquisition of the TWA task remained unaffected. These findings expand the knowledge in the regulation of cognitive abilities and may contribute to the understanding of the contraindicative effects of MO in anxiety related mental disorders.